Methylome-wide and meQTL analysis helps to distinguish treatment response from non-response and pathogenesis markers in schizophrenia - Polakkattil, Binithamol K.; Vellichirammal, Neetha N.; Nair, Indu V.; Nair, Chandrasekharan M.; Banerjee, Moinak (Frontiers in Psychiatry, 2024)
Schizophrenia is a complex condition with entwined genetic and epigenetic risk factors, posing a challenge to disentangle the intermixed pathological and therapeutic epigenetic signatures. To resolve this, we performed 850K methylome-wide and 700K genome-wide studies on the same set of schizophrenia patients by stratifying them into responders, nonresponders, and drug-naïve patients. The key genes that signified the response were followed up with real-time gene expression studies to understand the effect of antipsychotics at the gene transcription level. The study primarily implicates hypermethylation in therapeutic response and hypomethylation in the drug-nonresponsive state. Several differentially methylated sites and regions colocalized with the schizophrenia GWAS risk genes and variants, supporting the convoluted gene-environment association. Gene ontology and PPI network analysis revealed distinct patterns that differentiated the treatment response from drug resistance. The study highlights the strong involvement of several processes related to nervous system development, cell adhesion, and signaling in the antipsychotic response. The ability of antipsychotic medications to revert the pathology by modulating gene expression or methylation patterns is evident from the general increase in the gene expression of response markers and histone modifiers and the decrease in class II HLA genes following varying concentrations of medications like clozapine, olanzapine, risperidone, and haloperidol. The study indicates unidirectional overlap of methylation marks between pathogenesis and therapeutic response, thereby suggesting a careful distinction of methylation marks of pathogenesis from treatment response. In addition, there is a need to understand the tradeoff between genetic and epigenetic observations. It is suggested that methylomic changes brought about by drugs need careful evaluation for their positive effects on pathogenesis, course of disease progression, symptom severity, side effects, and refractoriness.